2004
DOI: 10.1121/1.1698815
|View full text |Cite
|
Sign up to set email alerts
|

Tunneling effect in sound transmission loss determination: Theoretical approach

Abstract: The aim of this study is to numerically evaluate a tunneling effect in the laboratory measurement of sound transmission loss. The tunneling effect arises from the depth of an aperture in the common wall between the source and receiving rooms. Variations of the sound transmission loss with the parameters of panel location, tunnel depth, and panel size are investigated. The difference in sound transmission loss is quite evident below the coincidence frequency and it greatly depends on the panel location in the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
20
0

Year Published

2008
2008
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 15 publications
3
20
0
Order By: Relevance
“…Regardless of the niche type, it is seen that negative differences become greater below 800 Hz as the niche depth increases, whereas positive and negative differences appear above 1 kHz in relation to the wavelength. The tendency at low frequencies is consistent with the previous experimental results and the theoretical explanations by Vinokur [11] and Kim et al [10]. Regarding the recessing niche, the variations of the STL difference reasonably well correspond with those for a larger glass pane in [12].…”
Section: Calculation Of Stlsupporting
confidence: 91%
See 2 more Smart Citations
“…Regardless of the niche type, it is seen that negative differences become greater below 800 Hz as the niche depth increases, whereas positive and negative differences appear above 1 kHz in relation to the wavelength. The tendency at low frequencies is consistent with the previous experimental results and the theoretical explanations by Vinokur [11] and Kim et al [10]. Regarding the recessing niche, the variations of the STL difference reasonably well correspond with those for a larger glass pane in [12].…”
Section: Calculation Of Stlsupporting
confidence: 91%
“…Some decades ago, several experimental studies demonstrated the niche effect [5][6][7][8][9], which was later investigated in theoretical and numerical studies [10][11][12][13]. So far, the following general findings on the niche effect have been obtained: 1) the effect is significant below the critical coincidence frequency; 2) the effect depends on the position of the specimen in the niche; 3) the lowest STL is obtained when the sample is located in the middle of the niche; 4) the highest STL is obtained when the sample is mounted flush at one of the edges of the niche; 5) the effect depends on the sectional shape of the niche around the specimen.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For finitely bounded constructions, the influence of boundary conditions and additional factors in relation to the finiteness of the structure on sound transmission is no longer negligible, promoting the search of effective and accurate modeling means. The transmission 23,24 or radiation 22 of sound through finite single-leaf panels have been discussed from different viewpoints. Sgard et al 36 and Panneton and Atalla 37 employed finite element method ͑FEM͒ models to predict sound-transmission loss ͑STL͒ across finite-sized, double-panel sound barrier with poroelastic linings.…”
Section: Introductionmentioning
confidence: 99%
“…Often, the experimental measurements do not possess reproducibility, and different STL curves from different laboratories were obtained even though the same panels were compared [38]. According to Kim et al [53], this may be attributed to the so-called tunneling effect, and the different mounting conditions adopted in different laboratories should be another key factor. On the other hand, to the authors' best knowledge, the problem of sound transmission through a double-panel partition with air cavity fully clamped (different from being simply supported) on its edges has not been analytically solved.…”
Section: Introductionmentioning
confidence: 99%